2020
DOI: 10.1021/jacs.0c01008
|View full text |Cite
|
Sign up to set email alerts
|

A Highly Water-Stable meta-Carborane-Based Copper Metal–Organic Framework for Efficient High-Temperature Butanol Separation

Abstract: Biofuels are considered sustainable and renewable alternatives to conventional fossil fuels. Biobutanol has recently emerged as an attractive option compared to bioethanol and biodiesel, but a significant challenge in its production lies in the separation stage. The current industrial process for the production of biobutanol includes the ABE (acetone−butanol−ethanol) fermentation process from biomass; the resulting fermentation broth has a butanol concentration of no more than 2 wt% (the rest is essentially wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
40
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 65 publications
(42 citation statements)
references
References 90 publications
2
40
0
Order By: Relevance
“…Over the last two decades, coordination polymers (CPs) have become one of the most attractive fields in chemistry because of their fascinating structures and promising applications as solid functional materials in adsorption and separation (Gan et al, 2020;Yang et al, 2020;Qian et al, 2020;Islamoglu et al, 2020), catalysis (Bavykina et al, 2020), sensing (Allendorf et al, 2020), luminescence (Rice et al, 2020) and magnetism (Thorarinsdottir & Harris, 2020;Wang et al, 2019b). Multicarboxylic acids have been employed to synthesize compounds comprising of various dimensional structures such as chains, layers and three-dimensional frameworks.…”
Section: Chemical Contextmentioning
confidence: 99%
“…Over the last two decades, coordination polymers (CPs) have become one of the most attractive fields in chemistry because of their fascinating structures and promising applications as solid functional materials in adsorption and separation (Gan et al, 2020;Yang et al, 2020;Qian et al, 2020;Islamoglu et al, 2020), catalysis (Bavykina et al, 2020), sensing (Allendorf et al, 2020), luminescence (Rice et al, 2020) and magnetism (Thorarinsdottir & Harris, 2020;Wang et al, 2019b). Multicarboxylic acids have been employed to synthesize compounds comprising of various dimensional structures such as chains, layers and three-dimensional frameworks.…”
Section: Chemical Contextmentioning
confidence: 99%
“…16,[18][19][20][21][22][23][24][25][26] In recent years we have reported that the introduction of hydrophobic carborane based linkers into MOFs greatly improve their hydrolytic stability for further practical application. 27 Icosahedral boranes [B 12 H 12 ] 2and carboranes 1,n-C 2 B 10 H 12 (n = 2, 7 or 12) are a class of commercially available and exceptionally stable 3D-aromatic boron-rich clusters that possess material-favorable properties such as thermal and chemical stability and high hydrophobicity. [28][29][30][31][32] The neutral carboranes are remarkably robust icosahedral boron clusters with two carbon and ten boron atoms.…”
Section: Introductionmentioning
confidence: 99%
“…Anchoring functionalized units on the pore wall of MOFs to enhance the host-guest interactions is also an effective method for separation [38][39][40] . This can theoretically selectively adsorb target molecule from the mixture under precise design on the functionalized units.…”
Section: Introductionmentioning
confidence: 99%